Recommendations for education and training of genetic nurses and counsellors in the United Kingdom. Issue 5 (May 1998) - Skirton, H; Barnes, C; Guilbert, P; Kershaw, A; Kerzin-Storrar, L; Patch, C; Curtis, G; Walford-Moore, J
Abstract : Genetic nurses and counsellors work as part of the professional team providing clinical genetic services from regional centres in the United Kingdom. The education and training needs of genetic nurses and counsellors have not previously been formally identified. The guidelines presented have been devised to equip practitioners to fulfil their professional role as defined in a previous study, by identifying objectives, educational pathways, and means of assessment. While academic courses provide an essential framework, experiential learning in a clinical setting is also considered a vital component of the preparation for practice.